1988
DOI: 10.1007/bf00274773
|View full text |Cite
|
Sign up to set email alerts
|

Early glomerular hyperfiltration and the development of late nephropathy in Type 1 (insulin-dependent) diabetes mellitus

Abstract: We performed a follow-up study of the glomerular function in a series of 29 Type 1 (insulin-dependent) diabetic patients who had been studied 18 years previously. Initial median duration of diabetes was 2 years (range 0-9) and at follow-up 21 (17-27) years. At follow-up, 8 diabetic patients exhibited increased urinary albumin excretion rate 515 (32-3234) micrograms/min with glomerular filtration rates significantly lower than 21 diabetic patients with normal urinary albumin excretion (85 vs 126 ml/min/1.73 m2;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
39
0

Year Published

1991
1991
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(42 citation statements)
references
References 32 publications
3
39
0
Order By: Relevance
“…One initially included report was subsequently removed from the analysis because it comprised patients with type 2 diabetes only, and as such was felt to be not comparable to the other studies [21]. In the end, ten cohort studies from six countries following 780 patients were included in this meta-analysis [22][23][24][25][26][27][28][29][30][31]. The publication years spanned three decades from 1984 to 2006 and all studies were of type 1 diabetic patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One initially included report was subsequently removed from the analysis because it comprised patients with type 2 diabetes only, and as such was felt to be not comparable to the other studies [21]. In the end, ten cohort studies from six countries following 780 patients were included in this meta-analysis [22][23][24][25][26][27][28][29][30][31]. The publication years spanned three decades from 1984 to 2006 and all studies were of type 1 diabetic patients.…”
Section: Resultsmentioning
confidence: 99%
“…It would therefore be essential to compare duration of diabetes at entry into the study, as patients with shorter disease duration are more likely to have hyperfiltration. The mean duration of diabetes at entry into the studies analysed was 8.1 years, but this ranged from 3.4 to 12.6 years [22,23]. Patients should therefore have been on established glycaemic therapy even in the studies with the shortest disease duration at baseline.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these four studies [3,11,16] reported a significant odds ratio for the association between baseline hyperfiltration and subsequent progression to at least microalbuminuria [7]. By contrast none of the remaining six studies [2,4,9,10,15,72] in the meta-analysis that used the conventional definition of microalbuminuria demonstrated a significant odds ratio. It is, therefore, possible that differences in the definition of microalbuminuria contributed to the significant relationship between hyperfiltration and progression of AER in the meta-analysis.…”
Section: Resolution Of Hyperfiltration In Clinical Trialsmentioning
confidence: 97%
“…Although patients with newly diagnosed type 1 diabetes may have increased AER at presentation, hyperfiltration usually precedes changes in albuminuria by several years [2]. However, it remains uncertain whether hyperfiltration is merely a marker of glycaemic control or whether it exerts a pathogenetic role in human diabetic nephropathy, independently of factors such as HbA 1c , blood pressure, age and pubertal status, duration of diabetes, AER and smoking [3,4]. Experimental models of hyperfiltration include hyperfiltration at the single-nephron level, in the whole kidney in the intact animal and in the remnant kidney after subtotal nephrectomy [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Prospective studies in type 1 and type 2 diabetic patients generally support the concept that normoalbuminuric and MA patients who progress have significantly higher baseline levels of blood pressure (25,39,43,44,47,(75)(76)(77) and HbA 1c (14,21,22,25,39,40,(43)(44)(45)47,(77)(78)(79) compared with patients that do not progress. However, there is still controversy as to whether increased baseline GFR is a predictor of progression (9,24,(80)(81)(82)(83)(84)(85). Preliminary results of our prospective study in normoalbuminuric type 1 diabetic patients have shown that patients who progress to MA or proteinuria have worse baseline glomerular lesions, lower GFR, and are more frequently hypertensive than patients remaining normoalbuminuric (33).…”
Section: Need For New Markers and Predictors Of Diabetic Nephropathy mentioning
confidence: 99%